Pengaruh Pelatihan Dan Pengembangan SDM Terhadap Kinerja Pegawai Di PT Kereta Api Indonesia (Persero) Daop 6 Yogyakarta - Latifah, Laili; Herlambang, Susatyo (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
This research aims to determine the effect of training and human resource development on employee performance at PT Kereta Api Indonesia (Persero) Daop 6 Yogyakarta. The research method used is a quantitative method with a descriptive approach. Data collection was carried out through questionnaires distributed to employees of PT Kereta Api Indonesia (Persero). The total population was 1953. Using purposive sampling techniques, a sample size of 95 respondents was obtained. The data analysis method uses multiple regression analysis to test the influence of training and development variables on employee performance. The research results show that the research variable Training (X1) has a partial influence on Employee Performance (Y) with a calculated t value of 4.046 and a t table of 1.986. Human resource development (X2) influences employee performance (Y) with a calculated t value of 2.226 and a t table of 1.986. Simultaneously (together) the variables Training (X1), HR Development (X2) influence Employee Performance (Y) at PT Kereta Api Indonesia (Persero) Daop 6 Yogyakarta. This is proven by the calculated F value of 29.415 which is greater than the F table of 3.10. Therefore, companies are advised to continue to optimize training and development programs in accordance with employee needs and developments in the transportation industry.